A tirosina como marcador de lesão intestinal na isquemia mesentérica - Contrin, Ligia Marcia (2005)
Introduction: The intestinal tract plays a central role in the protein catabolic response after infection or injury. Tyrosine (an index of overall proteolysis) and the release of lactate in intestinal luminal perfusate (ILP) during ligation of the superior mesenteric artery (SMA) were assessed. The present study aims to determine whether tyrosine flow from intracellular compartment to lumen could occur during ischemia induced-gut injury. Methods: Fourteen New-Zealand rabbits were allocated into 2 groups (group I: control (n=6) and group II: ischemia (n=8). SMA (QSMA) and aortic (Qaorta) flows were measured using ultrasonic flow probes. A segment from the ileum was isolated using two multilumen tubes with inflated balloons to delimit a closed segment to be perfused. In a second gut segment, a tonometric catheter (TRIP® Tonometry Catheter, Datex, Finland) was placed. Animals in group II were submitted to ligation of SMA after baseline measurements. The concentrations of tyrosine and lactate in intestinal lumen of both serum and perfusate were determined. Tyrosine was assayed by the fluorometric method as previously described. (1) Results: The lactate concentrations significantly increased in ILP after the ligation of SMA in 4 hours (from de 0.1 ± 0.7 mEq/L to 3.3 ± 1.6 mEq/L in 2 hours) compared to control group (from 0.1 ± 0.5 mEq/L para 0.3 ± 0.1 mEq/L in 2 hours) (p<0.05). Luminal tyrosine significantly increased during ischemia compared to control group in 2 hours (from 10.1 ± 7.7 mM/mL to 93 ± 63 mM/mL, group II; from 9.9 ± 7.8 mM/mL to 25.6 ± 24.0 mM/mL, group I, p<0.05). Conclusion: Tyrosine flow from intracellular compartment to lumen xiii occurred in this model suggesting ischemia-gut-derived proteolysis and a potential role for tyrosine as a marker of cell injury.